Effects of Hot-Air Drying Temperatures on Quality and Volatile Flavor Components of Cooked Antarctic krill (Euphausia superba) - Ruxin Zhang; Di Yu; Peng Wang; Yujun Liu; Hanfeng Zheng; Lechang Sun; Jie Zheng; Hai Chi (Foods)
Hot-air drying is a key step for Antarctic krill (Euphausia superba) onboard processing; however, few studies have explored the effects of different drying temperatures on the quality and flavor alternations of Antarctic krill. In this study, we investigated the effects of hot-air drying temperatures on the physicochemical properties and flavor of Antarctic krill. Sensory evaluation, as well as physical and chemical property tests, revealed that Antarctic krill treated with hot-air drying exhibited substantial changes in moisture status, lipid oxidation indices, and b* value. The sensory evaluation of Antarctic krill under high temperatures (120 °C and 150 °C) showed higher scores (8.45 ± 0.05 and 8.58 ± 0.22, respectively) on smells, whereas the color changes caused by high temperatures also resulted in lower overall sensory evaluation scores. The POV and TBARS values reached the highest at 26.63 ± 0.28 mg/g and 1.45 ± 0.19 mg/100 g, respectively. The b* value decreased significantly to 22.32 ± 4.56 following 150 °C treatment. Furthermore, a total of 53 volatile compounds were identified by GC-IMS, and the results showed that aldehydes, alcohols, alkanes, ketones, pyrazines, and furans were the main flavor sources of Antarctic krill. At the same time, the GC-MS results showed that the thermal process had no significant effect on the nutrient content of Antarctic krill. The findings obtained in this study provide foundational information for future research on ship-borne processing and high-value utilization of Antarctic krill.